2017
DOI: 10.3892/mmr.2017.7114
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 induces autophagy in human breast cancer cells through AMPK and the PI3K/Akt pathway

Abstract: Interleukin-12 (IL-12) serves an important role in immune responses and antitumor activity. The study of the association between autophagy and cancer cells remains controversial. The present study aimed to investigate the effect of IL‑12 on autophagy in the human breast cancer cell lines MDA‑MB‑231 and MCF‑7, and the possible molecular mechanism. Breast cancer cells were treated with different concentrations of recombinant IL‑12. The expression of the autophagy-associated protein microtubule‑associated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…For example, the blockade of PI3K–Akt by Slit2, which is secreted by stromal fibroblasts, significantly restrained breast cancer cell proliferation . Induction by interleukin‐12 and PI3K–Akt can activate autophagy and contribute to tumorigenesis, whereas mutations in the PI3K–Akt/mammalian target of rapamycin signaling pathway are frequently observed and are associated with a poor prognosis of breast cancer …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the blockade of PI3K–Akt by Slit2, which is secreted by stromal fibroblasts, significantly restrained breast cancer cell proliferation . Induction by interleukin‐12 and PI3K–Akt can activate autophagy and contribute to tumorigenesis, whereas mutations in the PI3K–Akt/mammalian target of rapamycin signaling pathway are frequently observed and are associated with a poor prognosis of breast cancer …”
Section: Discussionmentioning
confidence: 99%
“…The qRT-PCR results showed that miR-200a-3p, miR-200a-3p and Slit2, which is secreted by stromal fibroblasts, significantly restrained breast cancer cell proliferation. 23 Induction by interleukin-12 and PI3K-Akt can activate autophagy and contribute to tumorigenesis, 24 whereas mutations in the PI3K-Akt/mammalian target of rapamycin signaling pathway are frequently observed and are associated with a poor prognosis of breast cancer. 24 In the present study, we constructed an miRNA-mRNA interaction network to obtain an overview of the putative function of the most differentially expressed miRNAs.…”
Section: Dysregulated Expression Of Mir-200a-3p Mir-96-5p Mir-1-3mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly Jung et al (2014) showed that IL-12 is involved in antimicrobial action by activating the fusion of phagosome and lysosome via IFN-γ. Although IL-12-induced autophagy has been reported in breast cancer cells, human macrophages, and lung epithelial cells (Lin et al, 2017;Yang et al, 2018), the precise function of IL-12 in inducing this process…”
Section: Discussionmentioning
confidence: 99%
“…However, the possible mechanism by which HO-1/CO exerted a cytoprotective effect has not completely elucidated. In addition, as a major survival signaling pathway, activation of phosphatidylinositol 3-kinase (PI3K)/protein kinase B (Akt) resulted in the nuclear translocation of NF-E2 related factor 2 (Nrf2) and subsequently increased the expression of the downstream target gene, HO-1 (14,15). Additionally, phosphorylation of Akt at Ser473 via a PI3K-dependent pathway served a crucial role in regulating mitochondrial oxidative stress-mediated tissue injury (16,17).…”
Section: Introductionmentioning
confidence: 99%